GEO-STRATEGIC ANALYSIS OF IDENTITY POLITICS AND ETHNIC SEPARATISM: A RE-EVALUATION OF NIGERIA'S GOOD NEIGHBOURLINESS POLITICAL FRAMEWORK IN THE FACE OF TERRORISM - Adu, Funmilayo Modupe; Osadola, Oluwaseun Samuel (American Journal of International Relations, 2022)
Identity politics plays a major role in the survival, peace and continued existence of independent African states. This cannot but exist in a situation where ethnic groups were factionalized between geographical delineations of colonialism. Nigeria lies between five francophone countries with geo strategic, identity and security implications. This ipso facto connotes the idea of a split of ethno religious groups originally bounded in historical empires but now exist within the borders of colonially separated states. In this wise, Nigeria's good neighbourliness becomes an important political framework of interest. International terrorism since the wake of the 11th September attack on America has metalized into local terrorism perpetrated by the Boko Haram group in the case of Nigeria. Boko Haram terrorism has been internationalized with linkages with Isis and has spread its tentacles beyond the shores of Nigeria into neighbouring states of Chad, Niger, and Cameroon (countries which since the colonial era harboured Hausa, Fulani, Kanuri (Kanouri or Yerwa or Bare/Bari) and other such Nigerian northern ethnic groups with Islamic affiliations still binding the divided units since the Fulani jihad of the 18th century). Since Independence, Nigeria has wittingly dwelt within a choking Franco phony politics of survival. She had maintained a policy of good neighbourliness that has cost her continued friendship with France and economic openness to assist the African neighbours a breathing air of survival. In the wake of the new politics of international terrorism and with the spread of terrorist activities beyond the Nigerian borders into neighbouring States, this policy (good neighbourliness) becomes an agenda for analytical consideration, primarily because, relations between pre-colonial ethnic groups continue with a natural push and pull factor that post-colonial states cannot ignore. This is the relevance of this research paper which considers terrorism and identity politics within Nigeria's security challenge as implicative on good neighbourliness. The paper argues that, terrorism, identity politics are negatively implicated on the security of Nigeria and its neighbours and that the political framework of good neighbourliness needs to be reviewed to take care of new arising challenges.